The size, shape and borders of Serbia as essential factors in the security challenges of the Republic of Serbia - Lukić Darko (Politika nacionalne bezbednosti, 2024)
The paper discusses the size, shape and borders as a factor in the security of the territory of the Republic of Serbia. The illegal secession of Kosovo and Metohija represents an important security challenge that affects in a qualitative and quantitative sense the size, shape and border of the Republic of Serbia, as well as the defensive sensitivity of the territory. The problem was researched in the military-geographical and political-geographical domains. An analytical and synthetic approach was applied in the research of the problem through the comparison of the territory of the Republic of Serbia with the previous states that existed in our area in modern history. Graphical-analytical method as a general geographical method was applied in the consideration of qualitative and quantitative mathematical indicators of the territory. The research results showed that the small size, irregular shape and highly curved borders represent a problem for the defence of the territory of the Republic of Serbia. The Republic of Serbia, with an area of 88.361 km², ranks among small countries. The illegal secession of Kosovo and Metohija reduces the total area of the territory of the Republic of Serbia by 10.887 km². In a potential war conflict or aggression on the territory of the Republic of Serbia, space as a strategic factor of war would have a reduced importance for defence. Any loss of territory can have strategic implications for the entire course of the war. The semi-collected form acquires a southwest and southeast bulge corridor. From the territory of Kosovo and Metohija, the most core areas of the Republic of Serbia, such as the Pan-European transport corridor X can be threatened. The length of the border line to NATO members is 83.7% and 16.3% to militarily neutral states. The border shape coefficient is 1.98, which indicates a high degree of curvature of the border. Recommendations are given in the paper, the implementation of which would reduce the unfavourable geostrategic aspects of the size, shape and borders of the territory. Republic of Serbia. The priority is to change the strategic concept of defence, new military-territorial reorganization, demographic, cultural and geo-economic strengthening of the most sensitive parts of the territory of the Republic of Serbia.